2017
DOI: 10.1002/ajhb.22950
|View full text |Cite
|
Sign up to set email alerts
|

The historical spread of Arabian Pastoralists to the eastern African Sahel evidenced by the lactase persistence −13,915*G allele and mitochondrial DNA

Abstract: Even if the age of the most recent common ancestor of -13,915*G is ∼4 ka as shown in a previous study, our results suggest that its spread to Africa was more recent, which is consistent with the migrations of Arabic tribes. Because the incidence of sub-Saharan mtDNA haplotypes is negatively correlated with the occurrence of -13,915*G, we suggest that the decrease of its frequency in Africa has been caused by progressive admixture of the Arabian nomads with sub-Saharan populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 56 publications
6
30
0
Order By: Relevance
“…In fact, Arabic populations in Africa, that still maintain a nomadic way of life and keep camels (the Abbala), also have a higher frequency of the −13915*G variant and fewer L-type mtDNA haplogroups (predominantly observed in sub-Saharan Africa) than African Arabs keeping cattle (the Baggara). 87 On another hand, the Fulani pastoralists living in the western part of the Sahel/Savannah belt bear the same LP variant (−13910*T) as Eurasian populations 88,89 (Figure 2), which might be due to a common ancestral LP haplotype with Europeans. 90 It could be suggested that a higher consumption of fat contained in milk (and/or meat) of domesticated animals by these peoples shaped also the variation of genes involved in lipid metabolism, but thus far signals of selection at such genes have only been detected in populations living in the eastern part of the Sahel/Savannah belt.…”
Section: Lactase Persistence and Alumentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, Arabic populations in Africa, that still maintain a nomadic way of life and keep camels (the Abbala), also have a higher frequency of the −13915*G variant and fewer L-type mtDNA haplogroups (predominantly observed in sub-Saharan Africa) than African Arabs keeping cattle (the Baggara). 87 On another hand, the Fulani pastoralists living in the western part of the Sahel/Savannah belt bear the same LP variant (−13910*T) as Eurasian populations 88,89 (Figure 2), which might be due to a common ancestral LP haplotype with Europeans. 90 It could be suggested that a higher consumption of fat contained in milk (and/or meat) of domesticated animals by these peoples shaped also the variation of genes involved in lipid metabolism, but thus far signals of selection at such genes have only been detected in populations living in the eastern part of the Sahel/Savannah belt.…”
Section: Lactase Persistence and Alumentioning
confidence: 99%
“…The frequency of this allele displays a partially clinal pattern implying that it spread from Arabia to Africa very recently. In fact, Arabic populations in Africa, that still maintain a nomadic way of life and keep camels (the Abbala), also have a higher frequency of the − 13915*G variant and fewer L‐type mtDNA haplogroups (predominantly observed in sub‐Saharan Africa) than African Arabs keeping cattle (the Baggara) …”
Section: Genetic Evidence On Sahelian Populationsmentioning
confidence: 99%
See 3 more Smart Citations